Analisis Faktor-Faktor Penyebab Stres pada Mahasiswa Jurusan Biologi Angkatan 2022 Universitas Negeri Medan dalam Menyelesaikan Skripsi (Lembaga Pengembangan Kinerja Dosen, 2026)
This study aims to analyze the factors causing stress among Biology students of the 2022 cohort at Universitas Negeri Medan during the thesis preparation process. The study employed a quantitative approach using a survey method with 60 respondents, utilizing a Likert-scale questionnaire consisting of 20 statement items. Data were analyzed using Exploratory Factor Analysis (EFA) with the KMO and Bartlett tests to assess data feasibility. The results showed a KMO value of 0.643 and a Bartlett’s Test significance of 0.000, indicating that the data were suitable for factor analysis. The extraction process yielded five main factors contributing to student stress, namely academic pressure, social pressure, technical research obstacles, time management issues, and internal psychological conditions. The communalities values, most of which exceeded 0.55, confirmed that all indicators contributed strongly to factor formation. This study concludes that student stress during thesis writing is influenced by a combination of interconnected internal and external factors. The findings are expected to serve as a basis for the study program to improve academic services and psychological support for students.